PEMANFAATAN PANTAI PERANCAK SEBAGAI LOKASI AKTIVITAS LEISURE AND RECREATION DI DESA TIBUBENENG - Madjid, Karina Aprilia; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 3 No 2 (2015): VOL 3, NO 2 (2015): (JULY - DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2015.v03.i02.p06, 2015)
ABSTRACT The study, entitled "Utilization of Perancak Beach Location For Leisure And Recreation Activities in the Tibubeneng Village" is intended that the reader can get an idea of the potential Perancak Beach as the location of leisure and recreation activities in the Tibubeneng Village. This research includes an overview of the tourism potential of Perancak Beach, visitor motivation, and recreation meaning perceived by visitors who visit Perancak Beach. Data obtained through direct observation in Perancak Beach, interviews with those who did have detailed knowledge about Perancak Beach, and by distributing questionnaires to visitors to obtain data for the motivation and meaning of recreation they earn.
Keywords: leisure and recreation, motivation.